Hydrophobic polyvinyl alcohol nano-silver composite membrane as well as preparation method and application thereof

By using the method of treating enoki water extract and silver nitrate in the imitation lotus leaf template, a hydrophobic polyvinyl alcohol nanosilver composite film was prepared, which solved the problems of insufficient hydrophobicity of traditional PVA films and nanosilver preparation pollution, and achieved high-effect vegetable preservation.

CN119505455APending Publication Date: 2025-02-25JIANGSU POLYTECHNIC COLLEGE OF AGRI & FORESTRY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411491913.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing polyvinyl alcohol (PVA) films are insufficiently hydrophobic in fruit and vegetable preservation, and traditional nano silver preparation methods have environmental pollution and toxicity problems.

Method used

The hydrophobic polyvinyl alcohol nano-silver composite film was prepared by using enoki mushroom water extract, polyvinyl alcohol and silver nitrate as raw materials, and treated in a lotus leaf template through microwave reaction and ultraviolet irradiation.

Benefits of technology

The hydrophobicity of the membrane is improved, and the preparation of green, safe and pollution-free nano silver is achieved, which extends the storage time of fruits and vegetables and maintains their quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005100303470000011
    Figure HDA0005100303470000011
  • Figure HDA0005100303470000012
    Figure HDA0005100303470000012
  • Figure HDA0005100303470000013
    Figure HDA0005100303470000013
Patent Text Reader

Abstract

The invention discloses a hydrophobic polyvinyl alcohol nano-silver composite membrane as well as a preparation method and application thereof. Comprising the following steps: by taking a flammulina velutipes water extract, polyvinyl alcohol and silver nitrate as raw materials, carrying out microwave reaction, then putting into a lotus leaf-like template (PDMS film), and carrying out ultraviolet radiation. A PDMS film is used as a template, a needle mushroom water extract, polyvinyl alcohol and silver nitrate are added to obtain a mixed solution, and the polyvinyl alcohol nano-silver composite film with the bionic lotus leaf hydrophobic surface is prepared after the mixed solution is irradiated and dried by an ultraviolet lamp. The hydrophobicity of the polyvinyl alcohol nano-silver composite film is remarkably improved, and the effects of maintaining the quality, delaying decline and prolonging the storage time are found by wrapping the hericium erinaceus. By wrapping the hericium erinaceus, the weight loss ratio is reduced by 46.28%, the relative content of vitamin C is improved by 127.04%, the sugar degree is improved by 40.91%, the relative enzyme activity of POD is improved by 332.17%, the relative enzyme activity of CAT is improved by 286.25%, and the hericium erinaceus can be widely applied to fresh keeping of fruits and vegetables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrophobic polyvinyl alcohol nano-silver composite film and a preparation method and application thereof, belonging to the field of natural product development and application. Background Art

[0002] Polyvinyl alcohol (PVA) is a polymer material that can be mass-produced from non-petroleum raw materials. Due to the presence of a large number of hydrophilic groups (OH) in the PVA molecular chain, it has poor water resistance and has no antioxidant or antibacterial activity, which limits its application in the field of preservation. Nanosilver is a new antibacterial product based on nanomaterial technology. Although adding it to polyvinyl alcohol film can improve the mechanical properties and thermal stability of the film, the hydrophobicity has not been significantly improved. At the same time, chemical reduction is the most commonly used method for preparing nanosilver particles. Commonly used reducing agents include ascorbic acid, humic acid, borohydride, hypophosphorous acid, hydrazine hydrate, etc. Although this method is simple to operate and has low cost, it will cause certain pollution to the environment during the preparation process, and the chemicals therein will also increase certain toxicity, which will have a certain impact on the environment and the human body. Summary of the invention

[0003] Purpose of the invention: The first purpose of the present invention is to provide a polyvinyl alcohol composite film having a certain hydrophobic surface and using green prepared nanosilver as filler. The second purpose of the present invention is to provide a preparation method of the hydrophobic polyvinyl alcohol nanosilver composite film. The third purpose of the present invention is to provide the application of the hydrophobic polyvinyl alcohol nanosilver composite film in the preservation of fruits and vegetables.

[0004] Technical solution: The hydrophobic polyvinyl alcohol nano-silver composite film described in the present invention includes Flammulina velutipes water extract, polyvinyl alcohol, and silver nitrate as raw materials, which are placed in a lotus leaf imitation template after microwave reaction and obtained by ultraviolet irradiation.

[0005] Furthermore, the preparation method of the Flammulina velutipes water extract comprises the following steps:

[0006] The Flammulina velutipes is washed, frozen, and crushed to obtain Flammulina velutipes powder. Water is added to the Flammulina velutipes powder, and the mixture is heated for extraction to obtain an extract. The extract is filtered and filtered under reduced pressure. The filtrate is vacuum-frozen and dried to obtain the Flammulina velutipes extract.

[0007] Furthermore, the freezing is performed at a temperature below -20°C for more than 24 hours.

[0008] Furthermore, the mass ratio of Flammulina velutipes powder to water is 1:10 to 1:30.

[0009] Furthermore, the temperature of the heating extraction is 50-70° C., and the time of the heating extraction is 1-3 hours.

[0010] Furthermore, the preparation method of the lotus leaf imitation template comprises the following steps:

[0011] Pour PDMS glue into the lotus leaf as a template and let it dry naturally to obtain a lotus leaf imitation template.

[0012] The method for preparing the hydrophobic polyvinyl alcohol nanosilver composite film of the present invention comprises the following steps:

[0013] (1) dissolving polyvinyl alcohol in water, adding the Flammulina velutipes water extract to obtain a mixed solution, adjusting the pH of the mixed solution, adding a silver nitrate solution, and performing microwave heating to obtain a reaction solution;

[0014] (2) pouring the reaction solution into a lotus leaf-like template, irradiating with ultraviolet light, and drying to obtain a hydrophobic polyvinyl alcohol nanosilver composite film.

[0015] Furthermore, in step (1), the mass ratio of polyvinyl alcohol to Flammulina velutipes water extract to water is 1-5:1-5:100, the pH value of the mixed solution is 10-14, and the concentration of silver nitrate in the reaction solution is 0.12-0.28%.

[0016] Furthermore, in step (1), the power of microwave heating is 500 to 900 W, and the time of microwave heating is 20 to 100 S.

[0017] Furthermore, in step (2), the power of ultraviolet irradiation is 20 to 40 W, and the time of ultraviolet irradiation is 5 to 15 minutes.

[0018] Furthermore, in step (2), the drying temperature is 55 to 75° C., and the drying time is 2 to 4 hours.

[0019] The hydrophobic polyvinyl alcohol nano-silver composite film of the invention is used in the preservation of fruits or vegetables.

[0020] The present invention utilizes the widely available and low-cost Flammulina velutipes water extract to greenly prepare nanosilver, and prepares a polyvinyl alcohol nanosilver composite film with a certain hydrophobic surface for the preservation of fruit and vegetable products. While improving the resource utilization of Flammulina velutipes, it also provides a basis for developing safe, environmentally friendly and efficient fruit and vegetable packaging films.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0022] The invention prepares nano silver on the basis of obtaining the water extract of Flammulina velutipes by using the cheap and easily available Flammulina velutipes as raw materials. The prepared nano silver is used as a filler to simultaneously prepare a hydrophobic polyvinyl alcohol nano silver composite film. The preparation method is simple, easy to operate, green, safe and pollution-free. The composite film is wrapped to maintain the quality of Hericium erinaceus, delay decay and prolong the storage time. The hydrophobic polyvinyl alcohol nano silver composite film of the invention can be widely used in the preservation of fruits and vegetables. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The effect of different pH on the UV-visible spectrum of nanosilver;

[0024] Figure 2 This is the effect of different amounts of polyvinyl alcohol added on the UV-visible spectrum of nanosilver;

[0025] Figure 3 This is the effect of different amounts of Flammulina velutipes water extract added on the UV-visible spectrum of nanosilver;

[0026] Figure 4 This is the effect of different final concentrations of silver nitrate on the UV-visible spectrum of nanosilver;

[0027] Figure 5 The figure shows the effect of different microwave time on the UV-visible spectrum of nanosilver;

[0028] Figure 6 The infrared spectra of PVA-AgNPs composite film, pure PVA film and Flammulina velutipes water extract;

[0029] Figure 7 The scanning electron microscopy images of the cross-sections of PVA-AgNPs composite films and pure PVA films;

[0030] Figure 8 is the transmission electron microscopy image of PVA-AgNPs composite film;

[0031] Fig. 9 XRD patterns of PVA-AgNPs composite film and pure PVA film;

[0032] Fig.10 The contact angle diagrams of the hydrophobic surface of the PVA-AgNPs composite film and the pure PVA film;

[0033] Fig.11 This is the effect of PVA-AgNPs composite film, pure PVA film and no coating treatment on the weight loss rate of Hericium erinaceus during storage;

[0034] Fig.12 This is the effect of PVA-AgNPs composite film, pure PVA film and no coating treatment on the relative content of vitamin C in Hericium erinaceus during storage;

[0035] Fig.13 This is the effect of PVA-AgNPs composite film, pure PVA film and no coating treatment on the relative enzyme activity of POD enzyme during the storage of Hericium erinaceus;

[0036] Fig.14 This is the effect of PVA-AgNPs composite film, pure PVA film and no coating treatment on the relative enzyme activity of CAT enzyme during the storage of Hericium erinaceus;

[0037] Fig.15 Contact angle diagrams of composite films obtained by different preparation methods. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0039] Example 1

[0040] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0041] (2) Dissolve 4 g of PVA in 60 mL of distilled water, heat to about 90°C and stir for 30 min. Add 1 g of Flammulina velutipes water extract, stir and mix on a magnetic stirrer to obtain a mixed solution, drop a 20% NaOH solution into the mixed solution, and adjust the pH of the mixed solution to 10, 11, 12, 13 and 14, respectively. Then add 20% silver nitrate solution and adjust the volume to 100 mL, so that the final concentration of silver nitrate is 0.28%. Place the solution in a microwave reactor and microwave at 700 W for 40 s to prepare nanosilver and obtain a reaction solution.

[0042] (3) After the reaction is completed, the reaction solution is diluted 8 times and the absorption curve at 350-500 nm is measured using a UV-visible spectrophotometer. Figure 1 shown.

[0043] Figure 1 The effect of different pH on the UV-visible spectrum of nanosilver is shown in Figure 2. Figure 1 It can be seen that a strong characteristic absorption peak of nanosilver appears at a wavelength of 406nm, and the water extract of Flammulina velutipes can reduce silver nitrate to nanosilver. As the pH value increases, the ultraviolet absorption peak increases, and the peak value reaches the maximum at pH13.

[0044] Example 2

[0045] The preparation process is the same as in Example 1, specifically as follows:

[0046] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0047] (2) 1g, 2g, 3g, 4g and 5g of PVA were dissolved in 60mL of distilled water, heated to about 90°C and stirred for 30min. 1g of Enoki mushroom water extract was added respectively, stirred and mixed on a magnetic stirrer to obtain a mixed solution, and a 20% NaOH solution was added dropwise to the mixed solution to adjust the pH of the mixed solution to 13. Then 20% silver nitrate solution was added respectively and the volume was adjusted to 100mL, so that the final concentration of silver nitrate was 0.28%. The solution was placed in a microwave reactor and reacted at 700W for 40s to prepare nanosilver (AgNPs) to obtain a reaction solution.

[0048] (3) After the reaction is completed, the reaction solution is diluted 8 times and the absorption curve at 350-500 nm is measured using a UV-visible spectrophotometer. The results are as follows: Figure 2 shown.

[0049] Depend on Figure 2 It can be seen that with the increase of PVA addition, the peak value of the characteristic absorption peak of AgNPs is also increasing. When the PVA addition amount is 2g, the peak value of the absorption peak is the largest.

[0050] Example 3

[0051] The preparation process is the same as in Example 1, specifically as follows:

[0052] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0053] (2) Dissolve 2g of PVA in 60mL of distilled water, heat to about 90°C and stir for 30min. Add 1g, 2g, 3g, 4g and 5g of Flammulina velutipes water extract respectively, stir and mix on a magnetic stirrer to obtain a mixed solution, add a 20% NaOH solution dropwise to the mixed solution, and adjust the pH of the mixed solution to 13. Then add 20% silver nitrate solution and adjust the volume to 100mL, so that the final concentration of silver nitrate is 0.28%. Place the solution in a microwave reactor and react at 700W for 40s to prepare nanosilver to obtain a reaction solution.

[0054] (3) After the reaction is completed, the reaction solution is diluted 8 times and the absorption curve at 350-500 nm is measured using a UV-visible spectrophotometer. The results are as follows: Figure 3 shown.

[0055] Depend on Figure 3 It can be seen that when the amount of Flammulina velutipes water extract added increased from 1g to 5g, the peak value first increased and then decreased. When the amount of Flammulina velutipes water extract added was 2g, the peak value was the largest.

[0056] Example 4

[0057] The preparation process is the same as in Example 1, specifically as follows:

[0058] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0059] (2) Dissolve 2g of PVA in 60mL of distilled water, heat to about 90°C and stir for 30min. Add 2g of Flammulina velutipes water extract, stir and mix on a magnetic stirrer to obtain a mixed solution, drop a 20% NaOH solution into the mixed solution, and adjust the pH of the solution to 13. Then add 20% silver nitrate solution and adjust the volume to 100mL, so that the final concentration of silver nitrate is 0.12%, 0.16%, 0.2%, 0.24% and 0.28%, respectively. Place the solution in a microwave reactor and microwave at 700W for 40s to prepare nanosilver and obtain a reaction solution.

[0060] (3) After the reaction is completed, the reaction solution is diluted 8 times and the absorption curve at 350-500 nm is measured using a UV-visible spectrophotometer. The results are as follows: Figure 4 shown.

[0061] Depend on Figure 4 It can be seen that with the increase of the final concentration of AgN03, the peak value of the characteristic absorption peak of AgNPs first increases and then decreases. When the final concentration of AgN03 is 0.20%, the peak value of the absorption peak is the largest.

[0062] Example 5

[0063] The preparation process is the same as in Example 1, specifically as follows:

[0064] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0065] (2) Dissolve 2g of PVA in 60mL of distilled water, heat to about 90°C and stir for 30min. Add 2g of ethanol extract of Flammulina velutipes, stir and mix on a magnetic stirrer to obtain a mixed solution, drop a 20% NaOH solution into the mixed solution, and adjust the pH of the solution to 13. Add 20% silver nitrate solution and adjust the volume to 100ml, so that the final concentration of silver nitrate is 0.2%. Place the solution in a microwave reactor and microwave at 700W for 20s, 40s, 60s, 80s and 100s to prepare nanosilver and obtain a reaction solution.

[0066] (3) After the reaction is completed, the reaction solution is divided 8 times and the absorption curve at 350-500 nm is measured using a UV-visible spectrophotometer. The results are as follows Figure 5 shown.

[0067] Depend on Figure 5 It can be seen that the peak value of the absorption peak of AgNPs increases with the increase of microwave time. When the microwave reaction time is 60S, the peak value of the absorption peak is the largest.

[0068] Example 6

[0069] The preparation process is the same as in Example 1, specifically as follows:

[0070] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0071] (2) Dissolve 2 g of PVA in 60 mL of distilled water, heat to about 90 ° C and stir for 30 min. Add 2 g of Flammulina velutipes water extract, stir and mix on a magnetic stirrer to obtain a mixed solution, and add a 20% NaOH solution to the mixed solution until the pH is 13. Add 20% silver nitrate solution and adjust the volume to 100 mL, so that the final concentration of the silver nitrate solution is 0.20%. Place the solution in a microwave reactor and microwave at 700 W for 60 seconds to prepare nanosilver to obtain a reaction solution (AgNPs solution).

[0072] (3) Place a lotus leaf that fits the culture dish flatly in a culture dish with a diameter of 120 mm, pour in 20 mL of Dow Corning PDMS glue, and remove the film after natural drying for 24 hours to obtain a lotus leaf template, i.e., a PDMS film. The prepared PDMS film is placed in a culture dish of the above size as a template, and 25 mL of the prepared AgNPs solution is poured in. After irradiation with a 30W ultraviolet lamp for 10 minutes, it is placed in a 65°C oven and dried for 3 hours. Cool to room temperature and remove the film to obtain a nanosilver polyvinyl alcohol composite film (PVA-AgNPs composite film).

[0073] Comparative Example 1

[0074] Dissolve 2g PVA in 60mL distilled water, heat to about 90℃ and stir for 30min. Pour 25mL of the prepared PVA solution into a 120mm Petri dish, irradiate with a 30W UV lamp for 10min, and then place in a 65℃ oven to dry for 3h. Cool to room temperature and peel off the film to obtain a pure PVA film.

[0075] The enoki mushroom water extract prepared in Example 6, the PVA-AgNPs composite film and the pure PVA film prepared in Comparative Example 1 were subjected to infrared spectrum analysis. The results are as follows: Figure 6 shown.

[0076] Figure 6 The infrared spectra of PVA-AgNPs composite film, pure PVA film and Flammulina velutipes water extract are shown in Figure 2. Figure 6 It can be seen that pure PVA film at 1085cm -1 is the stretching vibration of CO bond in the amorphous region of PVA, at 3280cm -1 Corresponding to the stretching vibration of OH bond, 2912cm -1 Corresponding to the stretching vibration of -CH2, 1423cm -1 The corresponding CH-CH2 bending vibration peak. After adding nanosilver to PVA, the four characteristic peaks shifted to the low wavenumber direction, indicating that there is an interaction between the film-forming matrix PVA and nanosilver. The PVA-AgNPs composite film has a peak at 1561cm -1 The characteristic stretching vibration peak of -NO2 is shown at 1404cm -1 The peak at becomes stronger, indicating that there is van der Waals interaction between nanosilver molecules and the film-forming matrix PVA.

[0077] The PVA-AgNPs composite film prepared in Example 6 and the pure PVA film prepared in Comparative Example 1 were analyzed by scanning electron microscopy. Figure 7 shown.

[0078] Figure 7 The scanning electron microscope images of the cross-section of the PVA-AgNPs composite film and the pure PVA film. A is the pure PVA film, and B is the PVA-AgNPs composite film. Figure 7 It can be seen that compared with the cross-section of the PVA film, some pores and cracks are formed inside the PVA-AgNPs composite film due to the dispersion of nanosilver in the matrix.

[0079] The PVA-AgNPs composite film prepared in Example 6 was analyzed by transmission electron microscopy. Figure 8 shown.

[0080] Figure 8 The transmission electron microscope image of the PVA-AgNPs composite film. Among them, A is 50nm, B is 10nm, and C is 5nm. Figure 8 It can be seen that the silver nanoparticles in the PVA-AgNPs composite film are spherical or quasi-spherical, with a particle size between 2 and 10 nm. The particle distribution is relatively uniform, few particles are polydispersed, and agglomeration occurs in some places.

[0081] XRD analysis was performed on the PVA-AgNPs composite film prepared in Example 6 and the pure PVA film prepared in Comparative Example 1. The results are as follows: Fig. 9 shown.

[0082] Fig. 9The XRD patterns of PVA-AgNPs composite film and pure PVA film, where A is pure PVA film and B is PVA-AgNPs composite film. Fig. 9 It can be seen that the pure PVA film and the PVA-AgNPs composite film show obvious PVA crystal characteristic peaks at a diffraction angle of 19.6°. The prepared PVA-AgNPs composite film produces obvious standard silver crystal diffraction peaks at 38.2° and 44.3°.

[0083] The contact angle analysis was performed on the PVA-AgNPs composite film prepared in Example 6 and the pure PVA film prepared in Comparative Example 1. The results are as follows: Fig.10 shown.

[0084] Fig.10 The contact angle diagram of the hydrophobic surface of the PVA-AgNPs composite film and the pure PVA film. Fig.10 It can be seen that compared with the PVA film, the contact angle of the PVA-AgNPs composite film increased from 38.7°, which is hydrophilic, to 137.3°, which is close to the super-hydrophobic surface. Compared with the PVA film, the contact angle of the PVA-AgNPs composite film increased by 254.8%, and the hydrophobicity of the PVA-AgNPs composite film was significantly enhanced. This shows that the constructed hydrophobic surface successfully increased the contact angle of the membrane surface.

[0085] Example 7

[0086] Select fresh white, regular-shaped, and mechanically undamaged Hericium erinaceus. Divide Hericium erinaceus into two film-coated treatment groups (pure PVA film group (PVA film wrapped Hericium erinaceus), PVA-AgNPs composite film group (PVA-AgNPs composite film prepared in Example 6 wrapped Hericium erinaceus)) and one uncoated Hericium erinaceus as a blank control group, and put 10 Hericium erinaceus in each group into a tray. The samples were stored in a constant temperature box at 25°C (±2°C) for 6 days, and the weight loss rate, vitamin C content, POD enzyme activity, and CAT enzyme activity of Hericium erinaceus were measured every day. The results are as follows: Figure 11-14 shown.

[0087] Depend on Fig.11 It can be seen that the weight loss rate of the PVA-AgNPs composite membrane group samples increased at a lower rate than that of the other groups during storage. On the sixth day of storage, the weight loss rate of the PVA-AgNPs composite membrane group decreased by 35.89% and 46.28% compared with the pure PVA group and the blank control group, respectively.

[0088] Depend on Fig.12 It can be seen that on the 6th day of storage, the relative content of vitamin C in Hericium erinaceus wrapped with PVA-AgNPs composite film increased by 24.30% compared with Hericium erinaceus wrapped with pure PVA film, and the relative content of vitamin C increased by 127.04% compared with the blank control group.

[0089] Depend on Fig.13 It can be seen that on the 6th day of storage, compared with the pure PVA film group, the relative enzyme activity of Hericium erinaceus POD enzyme wrapped in PVA-AgNPs composite film increased by 74.20%; compared with the blank control group, the relative enzyme activity of Hericium erinaceus POD enzyme wrapped in PVA-AgNPs composite film increased by 332.17%.

[0090] Depend on Fig.14 It can be seen that the relative CAT activity of Hericium erinaceus wrapped with PVA-AgNPs composite film increased by 286.25% compared with the blank control group, and increased by 166.49% compared with Hericium erinaceus wrapped with pure PVA film.

[0091] Comparative Example 2

[0092] The preparation process is the same as that of Example 6, except that the Flammulina velutipes fermentation broth is used instead of the Flammulina velutipes water extract of the present application, wherein the Flammulina velutipes fermentation broth is prepared with reference to the published patent document CN111518849A (a method for synthesizing nanosilver using Flammulina velutipes fermentation product).

[0093] (1) Dissolve 2g of PVA in 60mL of distilled water, heat to about 90℃ and stir for 30min. Add 2mL of the prepared Flammulina velutipes fermentation broth, stir evenly on a magnetic stirrer to obtain a mixed solution, and drop a 20% NaOH solution into the mixed solution until the pH is 13. Add 20% silver nitrate solution and adjust the volume to 100mL, so that the final concentration of the silver nitrate solution is 0.20%. Place the solution in a microwave reactor and microwave at 700W for 60S to prepare nanosilver, and obtain a reaction solution (AgNPs solution).

[0094] (3) Place a lotus leaf that fits the culture dish flatly in a culture dish with a diameter of 120 mm, pour in 20 mL of Dow Corning PDMS glue, dry it naturally for 24 hours, and then peel off the film to obtain a lotus leaf template, i.e., a PDMS film. The prepared PDMS film is placed in a culture dish as a template, and 25 mL of the prepared AgNPs solution is poured in. After irradiation with 30 W ultraviolet light for 10 minutes, it is placed in a 65 ° C oven and dried for 3 hours. Cool it to room temperature and peel off the film to obtain a nanosilver polyvinyl alcohol composite film A.

[0095] Comparative Example 3

[0096] The preparation process is the same as that of Example 6, except that no PDMS membrane is used, and the prepared AgNPs solution is directly introduced into a culture dish for ultraviolet irradiation to form a film. The details are as follows:

[0097] (1) Wash and dry the Flammulina velutipes, freeze at -20°C for 24 hours, crush, add distilled water at a solid-liquid ratio of 1:20 (m / v), and extract in a 60°C water bath for 2 hours. After filtering, the filtrate is concentrated under reduced pressure and freeze-dried in vacuum to obtain a water extract.

[0098] (2) Dissolve 2 g of PVA in 60 mL of distilled water, heat to about 90 ° C and stir for 30 min. Add 2 g of Flammulina velutipes water extract, stir and mix on a magnetic stirrer to obtain a mixed solution, and add a 20% NaOH solution to the mixed solution until the pH is 13. Add 20% silver nitrate solution and adjust the volume to 100 mL, so that the final concentration of the silver nitrate solution is 0.20%. Place the solution in a microwave reactor and microwave at 700 W for 60 seconds to prepare nanosilver to obtain a reaction solution (AgNPs solution).

[0099] (3) Pour 25 mL of the prepared AgNPs solution into a 120 mm diameter petri dish, irradiate with a 30 W UV lamp for 10 min, and then place in a 65 ° C oven to dry for 3 h. Cool to room temperature and peel off the film to obtain the nanosilver polyvinyl alcohol composite film B.

[0100] Comparative Example 4

[0101] The preparation process is the same as that of Comparative Example 2, except that the PDMS membrane is not used, and the prepared AgNPs solution is directly introduced into the culture dish for ultraviolet irradiation to form a film. The details are as follows:

[0102] (1) Referring to the published patent document CN111518849A (a method for synthesizing nanosilver using Flammulina velutipes fermentation product), Flammulina velutipes fermentation liquid was prepared.

[0103] (2) Dissolve 2g of PVA in 60mL of distilled water, heat to about 90°C and stir for 30 minutes. Add 2mL of the prepared Flammulina velutipes fermentation broth, stir evenly on a magnetic stirrer to obtain a mixed solution, and drop a 20% NaOH solution into the mixed solution until the pH is 13. Add 20% silver nitrate solution and adjust the volume to 100mL, so that the final concentration of the silver nitrate solution is 0.20%. Place the solution in a microwave reactor and microwave at 700W for 60S to prepare nanosilver, and obtain a reaction solution (AgNPs solution).

[0104] (3) Pour 25 mL of the prepared AgNPs solution into a 120 mm diameter culture dish, irradiate with a 30 W ultraviolet lamp for 10 min, and then place in a 65 ° C oven to dry for 3 h. Cool to room temperature and peel off the film to obtain a nano-silver polyvinyl alcohol composite film C. The contact angle of the rough surface of the composite film was measured for the PVA-AgNPs composite film prepared in Example 6, the nano-silver polyvinyl alcohol composite film A prepared in Comparative Example 2, the nano-silver polyvinyl alcohol composite film B prepared in Comparative Example 3, and the nano-silver polyvinyl alcohol composite film C prepared in Comparative Example 4. The results are as follows: Fig.15 As shown. Fig.15It can be seen that the contact angle of the nano-silver polyvinyl alcohol composite film A is 115.0°, and the contact angle of the PVA-AgNPs composite film is 137.3°. By comparing the PVA-AgNPs composite film and the nano-silver polyvinyl alcohol composite film A, it can be seen that the hydrophobicity of the composite film prepared by the water extract of Flammulina velutipes in the present invention is higher than that of the composite film prepared by the fermentation product of Flammulina velutipes, indicating that the water transport effect of the composite film prepared by the present invention is more significant. The contact angle of the nano-silver polyvinyl alcohol composite film B is 69.7°. The contact angle of the nano-silver polyvinyl alcohol composite film C is 60.9°. It can be seen that the present invention uses the imitation lotus leaf template to significantly improve the hydrophobicity of the composite film finally obtained. The hydrophobic performance of the PVA-AgNPs composite film prepared by the present invention using the imitation lotus leaf template and adding nano-silver is much higher than the hydrophobicity of the polyvinyl alcohol composite film in the prior art, and it has the effect of maintaining the quality, delaying decay, and extending the storage time of the food preserved by it, and can be widely used in the preservation of fruits and vegetables.

Claims

1. A hydrophobic polyvinyl alcohol nanosilver composite film, characterized in that: The hydrophobic polyvinyl alcohol nano-silver composite film comprises enoki mushroom water extract, polyvinyl alcohol and silver nitrate as raw materials, is placed in a lotus leaf imitation template after microwave reaction, and is obtained by ultraviolet irradiation.

2. The hydrophobic polyvinyl alcohol nanosilver composite film according to claim 1, characterized in that: The preparation method of Flammulina velutipes water extract comprises the following steps: The Flammulina velutipes is washed, frozen, and crushed to obtain Flammulina velutipes powder. Water is added to the Flammulina velutipes powder, and the mixture is heated for extraction to obtain an extract. The extract is filtered and filtered under reduced pressure. The filtrate is vacuum-frozen and dried to obtain the Flammulina velutipes extract.

3. The hydrophobic polyvinyl alcohol nanosilver composite film according to claim 2, characterized in that: The freezing step is freezing at a temperature below -20°C for more than 24 hours, the mass ratio of the enoki mushroom powder to water is 1:10 to 1:30, the temperature for heating extraction is 50 to 70°C, and the time for heating extraction is 1 to 3 hours.

4. The hydrophobic polyvinyl alcohol nanosilver composite film according to claim 1, characterized in that: The preparation method of the lotus leaf imitation template comprises the following steps: Pour PDMS glue into the lotus leaf as a template and let it dry naturally to obtain a lotus leaf imitation template.

5. The method for preparing the hydrophobic polyvinyl alcohol nanosilver composite film according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving polyvinyl alcohol in water, adding the Flammulina velutipes water extract to obtain a mixed solution, adjusting the pH of the mixed solution, adding a silver nitrate solution, and performing microwave heating to obtain a reaction solution; (2) pouring the reaction solution into a lotus leaf-like template, irradiating with ultraviolet light, and drying to obtain a hydrophobic polyvinyl alcohol nanosilver composite film.

6. The preparation method according to claim 5, characterized in that: In step (1), the mass ratio of polyvinyl alcohol to Flammulina velutipes water extract to water is 1-5:1-5:100, the pH value of the mixed solution is 10-14, and the concentration of silver nitrate in the reaction solution is 0.12-0.28%.

7. The preparation method according to claim 5, characterized in that: In step (1), the power of microwave heating is 500-900W, and the time of microwave heating is 20-100S.

8. The preparation method according to claim 5, characterized in that: In step (2), the power of ultraviolet irradiation is 20 to 40 W, and the time of ultraviolet irradiation is 5 to 15 minutes.

9. The preparation method according to claim 5, characterized in that: In step (2), the drying temperature is 55 to 75° C. and the drying time is 2 to 4 hours.

10. Use of the hydrophobic polyvinyl alcohol nanosilver composite film according to any one of claims 1 to 4 in preserving fruits or vegetables.

Citation Information

Patent Citations

  • Method for synthesizing nano-silver by utilizing flammulina velutipes fermentation product

    CN111518849A